THE LETTERS OF LADY MARY WORTLEY MONTAGU - Brophy, Sarah (My University, 1996)
This study treats the letters of Lady Mary (Pierrepont) Wortley Montagu (1689-1762), an English aristocrat who produced a extensive body of writing, primarily during the first half of the eighteenth century. My approach to the letters is informed by poststructuralist feminist theory, in particular by Judith Butler's theory of gender as performance. It is my contention that when we consider how this specific eighteenth-century woman's subjectivity is generated by intersecting, heterogeneous discourses, we equip ourselves to examine the ample contradictions of her self-positioning in relation to eighteenth-century discourses of gender and to notions of identity, authority, and community. Throughout this discussion, then, I take into account the historical specificities of Montagu' s position, especially the ways in which upper-class status, literary conventions, and certain other discourses, namely Oriental ism and gossip, intersect with gender norms to produce and shape her subjectivity.
The introductory chapter begins by considering Montagu's place in the poetry of her contemporary Alexander Pope as well as by examining her resistance to the place he assigns her; this discussion highlights the limitations on women's participation in public discourse, demonstrating also how gender norms might be transformed when a woman seizes the right to speak and write. Next, I examine current critical commentary on the letters, showing how readers of Montagu have moved in recent years towards a model of gender as performance. I argue that the references critics of Montagu make to Judith Butler's theory of gender and identity as performative constructs fall short of the investigative potential these concepts offer. I then return to Butler's work in order to theorize the concepts of subversion and abjection. Subsequently, Montagu's "Autobiographical Romance," a fragmentary story, provides an cogent example of how Montagu's subversive strategies of self-definition are contingent on the violent denigration of other women.
Chapter 2 focuses on The Embassy Letters (1716-1718), which Montagu wrote during her term as English ambassadress in Turkey to correspondents in England and France. Here, the relationship Montagu's texts construct between the author and Turkish noblewomen emerges an ambivalent one, as her strategies for criticizing gender norms are shown to be marked by a reluctance to cast in her lot with a group defined within both Orientalism and gender ideology as inferior, passive, and, hence, appropriable. Chapter 3 examines the letters Montagu wrote while in England during the 1720s to her sister Lady Mar who was living in Paris. In this chapter, I look at Montagu's relationship to the discourse of gossip. Though Montagu attempts in some ways to claim gossip (and vanity or self-pride) as a positive resource for women's self-representational practices, she is also prompted to violently reject the very women whose transgressions she celebrates. In both cases, I argue that Montagu's strategy of relegating other women to an abject status, outside the norms of social and cultural intelligibility, works to make Montagu's own transgressions of gender norms seem more poised, and thus more acceptable, than they might otherwise appear. Nonetheless, we see in both sets of letters how Montagu's fierce impositions of distance between herself and other women are qualified by her longing for connectedness with their experiences, especially their moments of liberation.
Having worked through these issues in the two sets of letters, I arrive at the conclusion that Montagu' s approach to the "trope of the other woman," to use the term employed by Reina Lewis in her recent book on Western women's Orientalism (Gendering Orientalism [1996] 26), involves a disturbing violence directed against other women. One of the most valuable aspects of Montagu's letters, however, is that they allow us to see how this violence is generated by the discourses which shape Montagu's own abject, disenfranchized position in her society and culture, and not by an essentially closed attitude towards other women or other cultures on her part. In the end, I maintain that Montagu's representational strategies remain troubling in certain local instances to the dominant eighteenth-century English notion that women are inert, appropriable bodies, incapable of representing themselves or of participating in public discourse. But I also emphasize that feminist readers of Montagu need to challenge the exclusions that underwrite the subversive aspects of her epistolary discourse.
Keywords: English Language and Literature; English Language and Literature